Experimental Study on the Durability Characteristics of Several Vegetable Fiber Reinforced Concretes Exposed to Sodium Sulfate - Ziane, Sami; Khelifa, Mohammed-Rissel; Mezhoud, Samy; Beroual, Ahmed; Medaoud, Saber (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Recently, numerous plant fibers have been investigated as a means to reinforce concrete and replace synthetic fibers, thereby producing more eco-friendly concretes. The primary concern for these studies is the durability of the fibers in the external environment.
Keywords: reinforced concrete; hemp fibers; Alfa fiber; polypropylene fiber; durability; sulfatic attacks; żelbet; włókna konopne; włókna Alfa; włókna polipropylenowe; trwałość